(untitled) (Cadernos de Sociomuseologia, 2009)
RESUMO Há uma gota de sangue em cada museu: a ótica museológica de Mário Andrade (M.A.) é uma dissertação de mestrado que aborda o pensamento museológico do autor de Macunaíma através da análise de seus escritos, de sua coleção particular e de suas práticas à frente do Departamento de Cultura da cidade de São Paulo e do Serviço do Patrimônio Histórico e Artístico Nacional. Três questões orientam a presente dissertação: 1a. Até que ponto as propostas museológicas de M.A. representam consolidação ou rompimento com o pensamento modernista? 2a. Como se colocam na obra de M.A. as questões referentes à identidade nacional e cultura popular? 3a. Sendo o museu um lugar privilegiado de construção de memória, não seria também um baluarte da tradição? Em que sentido um museu pode ser ruptura? Como são tratadas as idéias de coleção e museu pelo poeta modernista? O enfrentamento destas questões, aliado ao entendimento de que a gota de sangue é gota de humanidade e sinal de historicidade presente nos museus, constitui a base desse estudo. ABSTRACT There is a drop of blood in every museum: The museological vision of Mário de Andrade is a masters dissertation which covers the musological thinking of the author of Macunaíma through the analysis of his writings, his own collection, and his work as head of the Department of Culture of the City of São Paulo and of the National Institute of Historical and Artistic Patrimony. Three questions give direction to this dissertation. 1. To what extent do the proposals of Mário de Andrade concerning museology represent a consolidation of, or a break with the modernist thought? 2. How are the questions concerning national identity and popular culture addressed in the work of Mário de Andrade? 3. Since the museum is a privileged place for the building of communal memory does it not also become a strong preserver of tradition? In What sense can a museum break with tradition? How are the ideas of collection and museum treated by the modernist poet? Addressing these questions, along with understanding that a “drop of blood” is a “drop of humanity” (and a sing of the historicity present in museums) constitutes the groundwork of this study.